An Investigation of the Coherence of Oral Narratives: Associations With Mental Health, Social Support and the Coherence of Written Narratives - Vanaken, Lauranne; Bijttebier, Patricia; Hermans, Dirk (Frontiers in psychology)
In a first research question, we examined whether the relations that are generally observed between the coherence of written autobiographical narratives and outcomes of mental health and social support, can be replicated for the coherence of oral narratives. Second, we studied whether the coherence of oral narratives is related to the coherence of written narratives. Pearson correlations and -tests were calculated on data of two separate studies to examine the research questions. First, only thematic coherence of oral narratives was significantly, although moderately, negatively associated to symptoms of depression, anxiety and negative social interactions. Second, the coherence of oral narratives was higher than the coherence of written narratives. Only the thematic coherence of oral narratives was positively associated with thematic and total coherence of written narratives. Furthermore, correlations between written and oral narratives were stronger for negative narratives as compared to positive narratives. The ability to elaborate emotionally and make meaning out of important life events in oral narratives is, to a certain extent, related to better mental health and more social support. Furthermore, thematic coherence may be a relatively stable feature of individuals' narrative styles that is reflected in narratives of different modalities. Nonetheless, these topics need to be further researched to overcome present limitations.